Functional and Metabolic Evaluation of the Athlete's Heart By Magnetic Resonance Imaging and Dobutamine Stress Magnetic Resonance Spectroscopy - Pluim, B. M.; Lamb, H. J.; Kayser, H. W. M.; Leujes, F.; Beyerbacht, H. P.; Zwinderman, A. H.; van der Laarse, A.; Vliegen, H. W.; de Roos, A.; van der Wall, E. E. (Circulation, 1998)
Background: The question of whether training-induced left ventricular hypertrophy in athletes is a physiological rather than a pathophysiological phenomenon remains unresolved. The purpose of the present study was to detect any abnormalities in cardiac function in hypertrophic hearts of elite cyclists and to examine the response of myocardial high-energy phosphate metabolism to high workloads induced by atropine-dobutamine stress. Methods and Results: We studied 21 elite cyclists and 12 healthy control subjects. Left ventricular mass, volume, and function were determined by cine MRI. Myocardial high-energy phosphates were examined by 31P magnetic resonance spectroscopy. There were no significant differences between cyclists and control subjects for left ventricular ejection fraction (59±5% versus 61±4%), left ventricular cardiac index (3.4±0.4 versus 3.4±0.4 L · min-1 · m-2), peak early filling rate (562±93 versus 535±81 mL/s), peak atrial filling rate (315±93 versus 333±65 mL/s), ratio of early and atrial filling volumes (3.0±1.0 versus 2.6±0.6), mean acceleration gradient of early filling (5.2±1.4 versus 5.8±1.9 L/s2), mean deceleration gradient of early filling(-3.1±0.9 versus -3.2±0.7 L/s2), mean acceleration gradient of atrial filling (3.6±1.8 versus 4.5±1.7 L/s2), and atrial filling fraction (0.23±0.06 versus 0.26±0.04, respectively). Cyclists and control subjects showed similar decreases in the ratio of myocardial phosphocreatine to ATP measured with 31P magnetic resonance spectroscopy during atropine-dobutamine stress (1.41±0.20 versus 1.41±0.18 at rest to 1.21±0.20 versus 1.16±0.13 during stress, both P=NS). Conclusions: Left ventricular hypertrophy in cyclists is not associated with significant abnormalities of cardiac function or metabolism as assessed by MRI and spectroscopy. These observations suggest that training-induced left ventricular hypertrophy in cyclists is predominantly a physiological phenomenon.